THE IMPLEMENTATION OF AUDIO LINGUAL METHOD IN TEACHING GRAMMAR - Dhion Meitreya Vidhiasi; Yoana Gita Pradnya Lengari (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2018)
This study is trying to implement the Audio-Lingual Method in teaching Maritime English in Akademi Maritim Nusantara Cilacap. The researcher wants to find the acceptable techniques of Audio-Lingual Method and the improvement of the students after the treatment. The students were split into two groups which are experiment and control group. The data were taken from the test result of Pre-Test and Final Test of those groups. The data were analyzed by statistics. The researcher describes the data by employing the theory of Audio-Lingual Method by Brown (1994). The result shows that repetition is the most acceptable technique used to teach Maritime English. The students show a great improvement between the Pre-Test and Final Test.